The initial training of science teachers in african countries: a systematic literature review - Soares, Diana (2022)
This study presents a systematic literature review (SLR) on the initial training of science teachers in Africa based on selected research articles, in the period 2000–2020, that emphasize the importance of surveying knowledge that goes beyond those that historically have a longer path in the building of scientific knowledge, such as that of European or North American countries. The analysis included a total of 31 articles from the Web of Science (WoS) and Scopus databases. The findings indicate a lack of knowledge, or at least visibility, considering the initial training of African teachers, particularly in developing countries. South Africa leads the number of publications. Within the five African countries implied in the SLR the following outputs were identified: (i) a division between teacher education research that is ‘place-based’ and one that uses (only) ‘universal theories’ (such as Vygotsky and Bandura); (ii) a tension between the application of student-centered learning and teaching models and more traditional classroom practices. Finally, the majority of articles highlight the importance of investing in further research around teacher education. Based on these outputs the importance of international cooperation in teacher education research articulating theory and practice to ensure a global and local perspective towards sustainable development is reinforced.